Pattern and quality of recording pre-admission drug treatment in paediatric patients. Issue 6001 (10th January 1976) - Whyte, J; Greenan, E
Abstract : The pattern and quality of recording drug use before admission was examined in children admitted to a paediatric unit over eight months. The preadmission drug intake (1-7 drugs/patient) was lower than that of adults. Antibiotics were the most frequently prescribed drugs, but mild analgesics and antihistamine preparations were commonly used, often without medical advice. The simultaneous administration of prescribed and non-prescribed drugs appeared to be as common in children as in adults. The number of drugs taken was related to the number of domicilary consultation received and the number of doctors seen as as to confirm that most doctors' visits result in the prescription of medicine. The transfer and recording of drug information was poor, owing principally to lack of communication between doctors and failure to detect self-medication, but the modern practices of self-referral to hospital and use of multiple prescribers have further reduced the information available. The use of a "current treatment card" is required if the full significance of iatrogenic disease in childhood is to be investigated.